Working Environment and Software Configuration Management Assimilation using Traceability Enhancement Technique - Iqbal, H.; Javed, A.; Majeed, M. N. (The Nucleus, 2015)
Software Configuration Management (SCM) Systems are very useful in coordinating group effort in large and complex software systems. As a result of change in user requirement, market needs, tools, technology or new business goals emanate out, changes are continuously induced while developing the software product. For change management, Traceability technique and SCM are two prominent practices in the software development process. SCM helps in managing configuration items while traceability helps in tracing the knowledge about the configuration items. In this paper we propose a model of the SCM system with the working environment when changes are introduced in multiple artifacts and by which high quality products are developed.